2021
DOI: 10.21203/rs.3.rs-246805/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Co-metabolic biodegradation of 4-bromophenol in mixture of pollutants system by Arthrobacter chlorophenolicus A6

Abstract: Brominated phenols are listed as priority pollutants, and are the key components of paper pulp wastewater together with nitrophenol and chlorophenol. However, the biodegradation of bromophenol in a mixed substrate system is very scanty. In the present investigation, simultaneous biodegradation kinetics of three substituted phenols (4-bromophenol, 4-BP; 4-nitrophenol, 4-NP; and 4-chlorophenol, 4-CP) were investigated using Arthrobacter chlorophenolicus A6. A 23 full factorial design was applied with varying 4-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…batch shake flask mode,Sahoo et al (2021b) examined the degradation of 4-CP, 4-NP, and 4-BP by A. chlorophenolicus A6. They observed that 4-NP was degraded more quickly than other compounds.…”
mentioning
confidence: 99%
“…batch shake flask mode,Sahoo et al (2021b) examined the degradation of 4-CP, 4-NP, and 4-BP by A. chlorophenolicus A6. They observed that 4-NP was degraded more quickly than other compounds.…”
mentioning
confidence: 99%